Workshop of Updating Insight for DAAM Journals Website - Yuhani, Yusof; Chuan, Zun Liang (PSM, UMP, 2022)
Data Analytics and Applied Mathematics (DAAM) is a new journal listed in MyJurnal that serves as an international platform for importing new research in mathematics and statistics disciplines.